Don Quijote y Rocinante: Un paralelismo textual con ecos iconográficos - Fernando Ruiz García (Vernacular: New Connections in Language, Literature, & Culture, 2021)
The present paper aims to highlight the relationship between Don Quixote and his steed Rocinante, which constitutes a direct parallel that will be extrapolated to the iconographic plane, varying depending on the historical moment. To achieve this objective we will establish a chronology of the main illustrated editions of Don Quixote, which analyzes the most important images of each character based on the art and thought of the respective period. Finally, the characterization of Rocinante as a reflection of the hidalgo will be explored in order to deepen the relationship between the two and justify the parallels observed in the previously analyzed representations.
Keywords: Don Quixote; Rocinante; iconography; parallelism; Golden Age; Cervantes